2024
DOI: 10.1101/2024.01.23.576797
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Forest growth resistance and resilience to the 2018-2020 drought depend on tree diversity and mycorrhizal type

Lena Sachsenmaier,
Florian Schnabel,
Peter Dietrich
et al.

Abstract: 1. The frequency of consecutive drought years is predicted to increase due to climate change. These droughts have strong negative impacts on forest ecosystems. Mixing tree species is proposed to increase the drought resistance and resilience of tree communities. However, this promising diversity effect has not yet been investigated under extreme drought conditions and in the context of complementary mycorrhizal associations and their potential role in enhancing water uptake. 2. Here, we investigate whether tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 119 publications
0
1
0
Order By: Relevance
“…Further, it is remarkable that this pattern for C:N was encountered both for AM and EM tree species, which suggests that, despite the higher hostspecificity of AMF in our study site (Ferlian et al, 2021), EM trees are not only linked to AMF through dual mycorrhization (see Figure S12; Heklau et al, 2021;Teste et al, 2019), but may also benefit from AMF richness. For instance, the dual mycorrhization of EM trees might be especially beneficial during dry periods (Querejeta et al, 2009), which might explain the advantage of these trees during droughts shown in Sachsenmaier et al (2024) for our study site. Last, EMF richness did not have any significant effect on the traits studied, which suggest that even though EMF diversity can affect the uptake of nutrients (Khokon & Meier, 2023), this does not necessarily have an effect on the leaf strategy of the tree.…”
Section: Discussionmentioning
confidence: 87%
“…Further, it is remarkable that this pattern for C:N was encountered both for AM and EM tree species, which suggests that, despite the higher hostspecificity of AMF in our study site (Ferlian et al, 2021), EM trees are not only linked to AMF through dual mycorrhization (see Figure S12; Heklau et al, 2021;Teste et al, 2019), but may also benefit from AMF richness. For instance, the dual mycorrhization of EM trees might be especially beneficial during dry periods (Querejeta et al, 2009), which might explain the advantage of these trees during droughts shown in Sachsenmaier et al (2024) for our study site. Last, EMF richness did not have any significant effect on the traits studied, which suggest that even though EMF diversity can affect the uptake of nutrients (Khokon & Meier, 2023), this does not necessarily have an effect on the leaf strategy of the tree.…”
Section: Discussionmentioning
confidence: 87%